2008
DOI: 10.1253/circj.cj-08-0249
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-3 Polyunsaturated Fatty Acid Levels Correlate With the Extent of Coronary Plaques and Calcifications in Patients With Acute Myocardial Infarction

Abstract: rogression of coronary atherosclerosis and rupture of unstable plaque are key processes in acute myocardial infarction (AMI). The extent of coronary artery disease has been well documented as a major prognostic factor in patients with AMI. Prevention and evaluation of the progression of atherosclerotic plaque volume is thus essential to both reduce cardiac events and estimate prognosis after AMI.Evidence that supplementation with n-3 polyunsaturated fatty acids prevents atherosclerosis-related cardiovascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Previous epidemiological studies reported that high n-3/n-6 PUFA levels and the EPA/ AA ratio are associated with a low rate of ischemic heart disease 12,13) . In addition, a sub-analysis of the JELIS and other studies suggested that a high serum EPA/AA ratio is significantly associated with a low incidence of cardiac death or myocardial infarction, and a low coronary plaque score 14,15) . We also showed that the serum EPA/AA ratio in obese patients is associated with monocyte expression of IL-10, an antiinflammatory M2 marker 16) .…”
Section: Study Protocolmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous epidemiological studies reported that high n-3/n-6 PUFA levels and the EPA/ AA ratio are associated with a low rate of ischemic heart disease 12,13) . In addition, a sub-analysis of the JELIS and other studies suggested that a high serum EPA/AA ratio is significantly associated with a low incidence of cardiac death or myocardial infarction, and a low coronary plaque score 14,15) . We also showed that the serum EPA/AA ratio in obese patients is associated with monocyte expression of IL-10, an antiinflammatory M2 marker 16) .…”
Section: Study Protocolmentioning
confidence: 97%
“…In serum, most fatty acids are esterified in cholesterol and TG (or phospholipids), and these lipids are incorporated in lipoproteins such as VLDL and LDL, while a small part of the fatty acids are in a non-esterified (free) form and are bound to albumin. The composition of serum fatty acids was determined by capillary gas chromatography 14,15) . The esterified and non-esterified (free) fatty acids of the serum total lipids were transesterified with methanolic hydrochloric acid.…”
Section: Study Protocolmentioning
confidence: 99%
“…Evidence that fish intake prevents atherosclerosis‐related cardiovascular disease have been accumulating 10,11 . A recent study has shown a significant inverse correlation between serum EPA or DHA concentrations and cardiovascular risk 12 . Furthermore, some studies showed that fish intake reduced the rates of incidence for diabetes in patients with metabolic syndrome, and reduced the rates of death in patients with type 2 diabetes 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ueeda et al reported that serum EPA levels were significantly associated with the extent of coronary plaques in patients with acute myocardial infarction. 30 The presence of high-risk coronary plaques (ie, LDP+PR) was associated with low serum EPA levels in the present EPA. These results suggest that even after at least 6 months of statin therapy, there remains a residual risk for coronary atherosclerotic progression that leads to future cardiovascular events, including ACS.…”
Section: Cta Associations Between Serum Pufas and Coronary Plaque Finmentioning
confidence: 61%